1999
DOI: 10.1038/21181
|View full text |Cite
|
Sign up to set email alerts
|

Poleward shifts in geographical ranges of butterfly species associated with regional warming

Abstract: letters to nature NATURE | VOL 399 | 10 JUNE 1999 | www.nature.com 579 between 270 and 4,000 ms after target onset) and to ignore changes in the distractor. Failure to respond within a reaction-time window, responding to a change in the distractor or deviating the gaze (monitored with a scleral search coil) by more than 1Њ from the fixation point caused the trial to be aborted without reward. The change in the target and distractors was selected so as to be challenging for the animal. In experiments 1 and 2 th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
1,532
9
25

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,951 publications
(1,660 citation statements)
references
References 11 publications
57
1,532
9
25
Order By: Relevance
“…Some insect species feeding on these plants have increased consumption and reduced growth (e.g., Bezemer and Jones, 1998;Veteli et al, 2002;Zvereva and Kozlov, 2006), and, therefore, may be subjected to natural enemies for a longer time under elevated CO 2 . Higher temperatures, on the other hand, may directly compensate for some of the negative effects of increased CO 2 ; increasing temperatures affect the distribution of some species by shifting ranges poleward and altitudinally upward (e.g., Parmesan et al, 1999;Battisti et al, 2005). The reason for these observed species range shifts can be a result of reducing extreme winter temperatures, increasing thermal sum, or subsequent changes in properties of the host plants.…”
Section: Discussionmentioning
confidence: 99%
“…Some insect species feeding on these plants have increased consumption and reduced growth (e.g., Bezemer and Jones, 1998;Veteli et al, 2002;Zvereva and Kozlov, 2006), and, therefore, may be subjected to natural enemies for a longer time under elevated CO 2 . Higher temperatures, on the other hand, may directly compensate for some of the negative effects of increased CO 2 ; increasing temperatures affect the distribution of some species by shifting ranges poleward and altitudinally upward (e.g., Parmesan et al, 1999;Battisti et al, 2005). The reason for these observed species range shifts can be a result of reducing extreme winter temperatures, increasing thermal sum, or subsequent changes in properties of the host plants.…”
Section: Discussionmentioning
confidence: 99%
“…Cramer & Leemans 1991;Harras & Prentice 2003), and observations and experiments (e.g. Hattenschwiler et al 1996;Parmesan 1996;Molau & Alatalo 1998;Parmesan et al 1999) have confirmed climate-induced changes in ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…It should be born in mind that although a wide range of taxa have been shown to respond to climate change (Crick et al 1997;Parmesan et al 1999;Thomas and Lennon 1999;Pounds 2001;Fitter and Fitter 2002), most short-term local changes are provoked by land-use modifications or by stochasticity in the abundance and distribution of species; thus, the assignment of causality is mainly inferential. Importantly, the negative effects of climate change will thus merely be 'additive' to ongoing and increasing human-induced pressures.…”
Section: Perspectivesmentioning
confidence: 99%